Potential value of preoperative fasting blood glucose levels in the identification of postoperative delirium in non-diabetic older patients undergoing total hip replacement: The perioperative neurocognitive disorder and biomarker lifestyle study - Liu, Siyu; Xv, Lizhu; Wu, Xiaoyue; Wang, Fei; Wang, Jiahan; Tang, Xinhui; Dong, Rui; Wang, Bin; Lin, Xu; Bi, Yanlin (Frontiers in Psychiatry, 2022)
Background: Postoperative delirium (POD) is a usual complication after total hip replacement. This study aims to explore the relationship between the preoperative fasting blood glucose (FBG) levels and POD in non-diabetic older patients undergoing total hip replacement. Methods: The study included a total of 625 patients undergoing elective total hip replacement under combined spinal and epidural anesthesia from PNDABLE study. The relationship between POD and preoperative FBG was analyzed by Logistic regression model. The associations of FBG with individual cerebrospinal fluid (CSF) biomarkers were detected by multivariable linear regression model controlling for age, gender and education level. The mediation effects were explored by Mediation analyses , while using sensitivity analysis to test the reliability and stability of the results. POD assessment was performed twice daily by a trained anesthesiologist at 9:00–10:00 am and 2:00–3:00 pm on postoperative day 1-7 days or before patients were discharged from the hospital. POD was defined by the Confusion Assessment Method (CAM), and POD severity was measured using the Memorial Delirium Assessment Scale (MDAS). Results: POD was detected in 10.2% (60/588) of the patients. Logistic regression analysis showed that after adjusting for age and education level, the increased level of FBG (OR 1.427, 95%CI 1.117-1.824, P=0.004), CSF P-tau (OR 1.039, 95%CI 1.019-1.060, P<0.001) and CSF T-tau (OR 1.013, 95%CI 1.009-1.018, P<0.001) were risk factors for POD and the increased levels of CSF Aβ42 (OR 0.996, 95%CI 0.994-0.998, P=0.001) was a protective factor for POD. Multivariable linear regression models showed that in the POD group, higher preoperative FBG levels were negatively correlated with CSF Aβ42 level (β=-0.290， P=0.028) while positively correlated with CSF P-tau (β = 0.384, P=0.004) and T-tau (β = 0.447, P<0.001). Mediated effect analysis showed that CSF T-tau (proportion= 17.1%) had an apparent mediation effect on the relationship between FBG and POD. Sensitivity analysis revealed that the results from the Logistic regression model and multivariable linear regression models were consistent with previous results. Conclusions: The increased preoperative FBG was a risk factor for POD in older patients without T2DM, and T-tau might mediate the relationship between FBG and POD.